2018
DOI: 10.9778/cmajo.20170126
|View full text |Cite
|
Sign up to set email alerts
|

Health care professionals' neckties as a source of transmission of bacteria to patients: a systematic review

Abstract: Background: There is growing concern that neckties worn by health care professionals may contribute to infections contracted in health care settings. We evaluated the evidence for health-care-associated infections resulting from neckties and whether the evidence is sufficient to warrant a tieless policy in Canada. Methods:We performed a systematic review to determine whether neckties worn by health care professionals colonize harmful pathogenic bacteria and whether they contribute to the spread of infection to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 21 publications
0
9
0
1
Order By: Relevance
“…It is also prudent to mention here that although studies have reported health care workers' white coats and neckties as potential vectors for patient-to-patient transmission of microbes [56][57][58][59], a recent systematic review from Pace-Asciak and colleagues reported weak evidence of contamination of neckties and no evidence of increased risk of health care-associated infections related to attire [60]. It has also been shown that institutional restrictions in wearing coats and ties, as in the "bare below the elbows" policy, did not change rates of hand contamination of doctors working in a general hospital [61].…”
Section: Attire An Easily Modifiable Part Of Clinician's Encountermentioning
confidence: 90%
“…It is also prudent to mention here that although studies have reported health care workers' white coats and neckties as potential vectors for patient-to-patient transmission of microbes [56][57][58][59], a recent systematic review from Pace-Asciak and colleagues reported weak evidence of contamination of neckties and no evidence of increased risk of health care-associated infections related to attire [60]. It has also been shown that institutional restrictions in wearing coats and ties, as in the "bare below the elbows" policy, did not change rates of hand contamination of doctors working in a general hospital [61].…”
Section: Attire An Easily Modifiable Part Of Clinician's Encountermentioning
confidence: 90%
“…Only one randomised controlled trial was identified in the published literature, which reported that there were no pathogenic microorganisms isolated from neckties. The remaining studies surveyed were case-control and case series studies, which reported that neckties were contaminated with non-pathogenic environmental bacteria but provided little evidence of greater contamination with pathogens than not wearing a necktie ( Pace–Asciak et al, 2018 ).…”
Section: Survey Methodologymentioning
confidence: 99%
“…MRSA can be transmitted through direct hand contact with contaminated body fluid or contaminated stethoscopes [8], identification badges [9], neckties [10], and white coats [11], all worn by healthcare workers (mainly doctors and medical students) and it can also be transmitted through contaminated surfaces. Interestingly, a study on one of the medical universities showed that the presence of MRSA on neckties was only detected on doctors and not the medical students [12].…”
Section: Introductionmentioning
confidence: 99%